How to Design and Enforce Tobacco Excises? - Petit, Patrick; Nagy, Janos (Washington, D.C. : International Monetary Fund, 2016)
Taxing tobacco can help raise much needed revenue and save lives, but it needs to be done well. This 'How-to' note provides guidance on the basics of tobacco taxation. How high should tobacco taxes be? Should we use ad valorem or specific taxes? What are the key elements of an efficient tax administration that will secure the tax base and prevent illegal trade? These are important questions that need to be addressed and this note provide a sound first step towards solid policy decisions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet